2003
DOI: 10.1016/s0002-9270(03)00295-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MELD, Child-Pugh, and Emory model for the prediction of survival in patients undergoing transjugular intrahepatic portosystemic shunting

Abstract: OBJECTIVES:Recently, new prognostic models (Model for End-Stage Liver Disease [MELD model] and Emory score) were proposed for the prediction of survival in transjugular intrahepatic portosystemic shunt (TIPS) patients. Although the MELD model is considered to be superior and has consecutively been applied to priority listing for liver transplantation, these models have never been directly compared in terms of long-term prognosis. We therefore compared the prognostic accuracy of the different models, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 27 publications
(56 reference statements)
5
83
3
1
Order By: Relevance
“…The CTP score performed relatively well compared with the MELD score in all categories and was an independent predictor of 1-year mortality even after adjusting for the MELD score. Other authors have recently reported that both the MELD and CTP scores are fairly equivalent for predicting intermediate and short-term mortality in patients with cirrhosis [19] and in patients with advanced liver disease undergoing TIPS [20,21] although one study did show a superior discrimination power of MELD compared to CTP scores for predicting early mortality after TIPS [22]. The independent predictive ability of the CTP score may be because unlike the MELD score it accounts for hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 97%
“…The CTP score performed relatively well compared with the MELD score in all categories and was an independent predictor of 1-year mortality even after adjusting for the MELD score. Other authors have recently reported that both the MELD and CTP scores are fairly equivalent for predicting intermediate and short-term mortality in patients with cirrhosis [19] and in patients with advanced liver disease undergoing TIPS [20,21] although one study did show a superior discrimination power of MELD compared to CTP scores for predicting early mortality after TIPS [22]. The independent predictive ability of the CTP score may be because unlike the MELD score it accounts for hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 97%
“…This is supported by the majority of studies that show an inferiority of the CTP score in comparison with MELD. [23][24][25][26][27] However, some authors question these findings and show that CTP might be at least equally predictive compared with MELD. 23,28 -30 In addition, we demonstrated that sTNF-R 75 serum levels and MELD were significantly more accurate than the sTNF-R 75/55 ratio in predicting short-term survival at 6 months ( Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In predicting the outcomes of patients with cirrhosis, the Model for End-Stage Liver Disease (MELD) has been shown to be superior to the traditional Child-Pugh classification and other systems of risk stratification (5,6). Several studies have shown that hyponatremia is a strong predictor of early mortality, independent of MELD score (7).…”
Section: Introductionmentioning
confidence: 99%